2019
DOI: 10.1093/nop/npz004
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy is associated with improved survival and decreased neurologic death after SRS for brain metastases from lung and melanoma primaries

Abstract: Background The effect of immunotherapy on brain metastasis patients remains incompletely understood. Our goal was to evaluate its effect on survival, neurologic death, and patterns of failure after stereotactic radiosurgery (SRS) without prior whole-brain radiation therapy (WBRT) in patients with lung and melanoma primaries metastatic to the brain. Methods We performed a retrospective analysis of 271 consecutive lung or melan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 32 publications
4
35
0
Order By: Relevance
“…In addition, Diao et al reviewed 91 melanoma patients treated with SRS for brain metastases and showed that patients who received ipilimumab had better OS than patients who did not received ipilimumab (median OS 15.1 months vs 7.8 months, p = 0.02) 97 . Besides, similar results have been reported in some other retrospective studies 98 - 100 . Therefore, ICI-SABR is a promising strategy for metastatic melanoma and several phase I/II clinical trials are underway to further confirm the safety and efficacy of this combination (NCT03354962, NCT02858869, and NCT02716948).…”
Section: Synergistic Effect Of Sabr and Immune Checkpoint Inhibitosupporting
confidence: 91%
“…In addition, Diao et al reviewed 91 melanoma patients treated with SRS for brain metastases and showed that patients who received ipilimumab had better OS than patients who did not received ipilimumab (median OS 15.1 months vs 7.8 months, p = 0.02) 97 . Besides, similar results have been reported in some other retrospective studies 98 - 100 . Therefore, ICI-SABR is a promising strategy for metastatic melanoma and several phase I/II clinical trials are underway to further confirm the safety and efficacy of this combination (NCT03354962, NCT02858869, and NCT02716948).…”
Section: Synergistic Effect Of Sabr and Immune Checkpoint Inhibitosupporting
confidence: 91%
“…2 With the advances in immunology, immunotherapy has shown excellent outcomes in various diseases, especially melanoma. 3 However, patient responses to nivolumab therapy have been reported to range from 10% to 20%. 4 In most melanoma patients, clinical survival is reduced due to the metastases of advanced tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The most effective therapy to treat melanoma is surgical resection 2 . With the advances in immunology, immunotherapy has shown excellent outcomes in various diseases, especially melanoma 3 . However, patient responses to nivolumab therapy have been reported to range from 10% to 20% 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with metastatic NSCLC showed a similar pattern: Magnuson et al presented in a retrospective multiinstitutional analysis that patients who received upfront SRS followed by epidermal growth factor receptor (EGFR) TKI had superior outcome concerning OS compared to the patients who received EGFR-TKI primarily, with SRS as a salvage option [36]. Another study by Lanier et al suggests that immunotherapy after SRS improves OS and reduces the rate of neurological deaths of patients with melanoma or NSCLC [37]. In addition to the bene ts in treatment outcome, SRS also offers practical advantages for oncological treatments in general: by limiting the duration of the treatment to one day (compared to two weeks for WBRT with 30 Gy in 10 fractions), the systemic treatment does not have to be paused or postponed for too long, so that treatment can be started or continued in cases of acute systemic progression.…”
Section: Discussionmentioning
confidence: 93%